Lyophilized powder of calf bone marrow hydrolysate liposomes improved renal anemia: In vitro and in vivo evaluation. - Li Li; Shasha Zhao; Xiaodun Liu; Zhe Xu; Dong Li; Xiaoyu Dai (PLoS ONE)
This study aimed to find whether oral administration of calf bone marrow hydrolysate liposomes (CBMHL) can improve renal anemia. Calf bone marrow was defatted, papain hydrolyzed, liposomalized and lyophilized. Its hematopoietic ability was proved by the colony formation experiment of umbilical cord blood hematopoietic stem cells in vitro. The rat model of renal anemia was established by adenine intragastric administration, and different concentrations of CBMHL were intragastricly administrated. Blood routine and serological indexes, transcription levels of hematopoietic factors and renal pathology were detected. From the appearance, redispersability, water content, liposome indexes and stability of Lyophilized powder of CBMHL, it could be concluded that the quality of freeze-dried CBMHL powder under this freeze-drying process was good. Compared with the control group, the burst forming unit-erythroid (BFU-E) in the CBMHL group was larger and the number of colonies increased significantly in the colony formation experiment (P < 0.05). The results of lyophilized powder of CBMHL co-culture with human adipose mesenchymal stem cells (MSCs) and human cytokine-induced killer (CIK) cells showed that the lyophilized powder of CBMHL had no potential toxicity and allergic reaction in vitro. Compared with the Model Group, the red blood cell (RBC) count, hemoglobin (HB) content and hematokrit (HCT) of rats blood routine in the Model+high doses of CBMHL Group (Model+H-CBMHL Group) increased significantly (P < 0.05). Serum erythropoietin (EPO) and glutathione (GSH) levels increased significantly (P < 0.05), while serum creatinine (Cr) levels decreased significantly(P < 0.05). The transcription level of Epo in kidney increased significantly (P < 0.05), the transcription levels of erythropoietin receptor (Epor) in bone marrow and interleukin 6 (Il6) in spleen were significantly increased (P < 0.01). The fragility of red blood cells decreased significantly, and the pathological structure of kidney improved significantly. It was proved that lyophilized powder of CBMHL could effectively enhance the hematopoietic ability of rats with renal anemia and protect the kidney structure and function.